Attachment theory in practice : emotionally focused therapy (EFT) with individuals, couples, and families - Johnson, Susan M. (New York : The Guilford Press, 2019)
"Drawing on cutting-edge research on adult attachment--and providing an innovative roadmap for clinical practice--Susan M. Johnson argues that psychotherapy is most effective when it focuses on the healing power of emotional connection. The primary developer of emotionally focused therapy (EFT) for couples, Johnson now extends her attachment-based approach to individuals and families. The volume shows how EFT aligns perfectly with attachment theory as it provides proven techniques for treating anxiety, depression, and relationship problems. Each modality (individual, couple, and family therapy) is covered in paired chapters that respectively introduce key concepts and present an in-depth case example. Special features include instructive end-of-chapter exercises and reflection questions. "--
"Subject Areas/Keywords: attachment-based psychotherapy, couple therapy, family therapy, adult attachment, romantic relationships, sexual relationships, child-parent relationships, Dr. Sue Johnson, assessments, emotions, insecurity, insecure attachments, avoidant, anxious, ambivalent, disorganized, affect regulation, marital therapy, therapeutic alliance, humanistic, experiential, EFFT, EFIT, depression, anxiety, emotional disorders, treatments, interventions, techniques, attachment science, attachment therapy, attachment styles, John Bowlby, Carl Rogers, clinical applications, treating marital problems, marriage, love, family problems, safe and sound, early childhood experiences, childhood memories, family of origin, caregiving, counseling, resources for psychotherapists, guides for counselors, EFT manuals, psychotherapy integration, emotion and change DESCRIPTION Drawing on cutting-edge research on adult attachment--and providing an innovative roadmap for clinical practice--Susan M. Johnson argues that psychotherapy is most effective when it focuses on the healing power of emotional connection. The primary developer of emotionally focused therapy (EFT) for couples, Johnson now extends her attachment-based approach to individuals and families. The volume shows how EFT aligns perfectly with attachment theory as it provides proven techniques for treating anxiety, depression, and relationship problems. Each modality (individual, couple, and family therapy) is covered in paired chapters that respectively introduce key concepts and present an in-depth case example. Special features include instructive end-of-chapter exercises and reflection questions"--
Includes bibliographical references (pages 249-268) and index.
Keywords: Family psychotherapy; Marital psychotherapy; Psychotherapy; PSYCHOLOGY / Psychotherapy / General; MEDICAL / Psychiatry / General; SOCIAL SCIENCE / Social Work; RELIGION / Counseling; PSYCHOLOGY / Psychotherapy / Couples & Family